2019
DOI: 10.1371/journal.pone.0216468
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for emotional and behavioral problems in moderately-late preterms

Abstract: Objective To assess which factors, including maternal, lifestyle, pregnancy- and delivery-related, fetal and neonatal factors adjusted for socio-economic status, are related to emotional and behavioral problems in moderately-late preterm born children (MLPs; gestational age 32.0–35.9 weeks) at 4 years of age. MLPs are at greater risk of emotional and behavioral problems than full-term born children. Especially for MLPs, knowledge about factors that increase or decrease the risk of emotional and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
(78 reference statements)
0
3
0
1
Order By: Relevance
“…This may have biased the published results towards the null, if cannabis use/exposure was under-reported more often among those with child experiencing cognitive and behavioral problems. On the other hand, many reports did not adjust for prenatal exposure to tobacco, an important covariate that is strongly associated with both the exposure [ 90 ] and various cognitive [ 91 , 92 ] and behavioral [ 93 , 94 , 95 , 96 , 97 , 98 ] problems in the offspring, which may result in a bias away from the null.…”
Section: Discussionmentioning
confidence: 99%
“…This may have biased the published results towards the null, if cannabis use/exposure was under-reported more often among those with child experiencing cognitive and behavioral problems. On the other hand, many reports did not adjust for prenatal exposure to tobacco, an important covariate that is strongly associated with both the exposure [ 90 ] and various cognitive [ 91 , 92 ] and behavioral [ 93 , 94 , 95 , 96 , 97 , 98 ] problems in the offspring, which may result in a bias away from the null.…”
Section: Discussionmentioning
confidence: 99%
“…We found that SHIP was associated with higher internalizing scores in children, indicating more emotional development problems in children. Several previous studies have found associations between maternal infection during pregnancy and increased risk of emotional and behavioral problems in children through disruption of blood vessel formation between placenta and fetus that have long-term implications on development [ 26 , 32 , 50 ]. Maternal infection in pregnancy activates the mothers’ inflammatory immune response; several studies have identified this increase in inflammation as the mechanism that leads to increased risk of behavioral problems and disorders in offspring [ 51 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…It contrasts with the fact that there is published evidence on the best handling of psychosocial problems (e.g. [14][15][16][17]). This incorrect assumption prevents pediatricians from making use of existing evidence.…”
Section: Interpretation Of Main Findingsmentioning
confidence: 91%